2020
DOI: 10.1111/obr.13013
|View full text |Cite
|
Sign up to set email alerts
|

Third‐wave cognitive behaviour therapies for weight management: A systematic review and network meta‐analysis

Abstract: This systematic review and network meta-analysis synthesized evidence on the effects of third-wave cognitive behaviour therapies (3wCBT) on body weight, and psychological and physical health outcomes in adults with overweight or obesity.Studies that included a 3wCBT for the purposes of weight management and measured weight or body mass index (BMI) pre-intervention and ≥ 3 months postbaseline were identified through database searches (MEDLINE, CINAHL, Embase, Cochrane database [CENTRAL], PsycINFO, AMED, ASSIA, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
77
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 68 publications
(85 citation statements)
references
References 79 publications
3
77
0
Order By: Relevance
“…This is problematic given theorizing that ACT would support long-term behavior change, and this study only used a short term follow up assessment of 8 weeks. Prior studies have found long-term improvements when ACT is delivered in an in-person format [8,10], but long-term effects have not been studied with selfguided ACT. Similarly, psychological inflexibility failed to mediate the effects of ACT on the primary healthy eating outcome due to a non-significant relation between psychological inflexibility and this measure.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This is problematic given theorizing that ACT would support long-term behavior change, and this study only used a short term follow up assessment of 8 weeks. Prior studies have found long-term improvements when ACT is delivered in an in-person format [8,10], but long-term effects have not been studied with selfguided ACT. Similarly, psychological inflexibility failed to mediate the effects of ACT on the primary healthy eating outcome due to a non-significant relation between psychological inflexibility and this measure.…”
Section: Discussionmentioning
confidence: 99%
“…A growing body of research indicates the potential benefits of Acceptance and Commitment Therapy (ACT) [7] for diet, physical activity, and weight loss [8][9][10][11][12]. ACT is a modern cognitive behavior therapy (CBT) that aims to reduce maladaptive behavior regulatory effects of cognition, affect, and other internal experiences (i.e., psychological inflexibility) through acceptance and mindfulness-based methods, while increasing adaptive motivators for behavior through values-based methods [7].…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Looking forward, the therapeutic container for such work could be the ACE model (Accept, Connect, Embody) which was used to support patients undergoing psilocybin treatment for depression (Watts and Luoma, 2020) and is based on Acceptance and Commitment Therapy or ACT (A-Tjak et al, 2015). In fact, Walsh and Thiessen (2018) have also proposed that psychedelic therapy should incorporate Acceptance and Commitment Therapy, a framework which has also been used for different mental and physical health problems, including obesity (Lawlor et al, 2020) and depression (Bai et al, 2020). Alternatively, as highlighted above,…”
Section: From Addiction To Behavior Change Interventions Using Psychedelicsmentioning
confidence: 99%
“…We excluded the developed CBT studies such as thirdwave CBT from our CBT criteria. Third-wave CBTs such as mindfulness-based cognitive therapy and dialectical behavioral therapy have recently been used for treating obesity 25,26) ; however, these focus on the processes of acceptance, mindfulness, attention, or value 27) that exceeds the traditional CBT criteria. We excluded studies comparing CBT with no treatment, pharmacological intervention treatment, or surgical treatment.…”
Section: Study Selection (Inclusion and Exclusion Criteria)mentioning
confidence: 99%